The Marketing of The President : Political Marketing as Campaign Strategy - Newman, Bruce I (Sage Publications, 1994)
Using the 1992 presidential election as a case study, this book reveals how the American political process has been transformed by the use of marketing techniques. The author addresses issues of serious concern to the health of the political process including the role of polling, direct mail and television advertising. This is the first comprehensive account of the influence of marketing in a presidential election campaign